Narrative desire and the Book of Ruth - Powell, Stephanie Day (Library of Hebrew bible/Old Testament studies, 2018)
Narrative desire and the Book of Ruth -- Resistance: ambiguity and artistry in the Book of Ruth -- Rupture: Ruth and fried green tomatoes -- Reclamation: Ruth and oranges are not the only fruit -- Re-engagement: Ruth and Golem, the spirit of exile -- (Un)final gleanings